Studies on the Response of Silicon on Chlorophyll Fluorescence, Membrane Stability, Plant Water Status and Yield of Rice Genotypes under Drought - Gokulraj, N.; Ravichandran, V.; Boominathan, P.; Soundararajan, R. P. (Cutting-edge Research in Agricultural Sciences Vol. 3, 2020)
A field experiment was conducted during kharif season of 2017 to study the effect of silicon on membrane stability, plant water status and yield of rice genotypes under drought at Department of Rice, Tamil Nadu Agricultural University, Coimbatore. It is observed from the present study, Maximum membrane stability index (MSI) (93.1) was observed in CB06803 and minimum (86.2) in CB08702 under the control, when drought influenced, Sahbhagidhan retained the maximum MSI (79.8) with lower Malondialdehyde (MDA) content (0.68 µmol g-1) and IR64 fetched the lower MSI (67.6) with lower (MDA) (1.75 µmol g-1). Foliar spray of Silicon (Silixol 0.6%) under drought increased the MSI to maximum (88.4) in Sahbhagidhan wherein minimum (78.7) was observed in CB13805. In the aspect of plant water status, a greater decrease of 18% in RWC under drought, with lower the reduction in drought tolerant check Sahbhagidhan (14.5%). Foliar spray of silicon (Silixol 0.6%) under drought increased the RWC by 12% with greater the increase in genotype CB13805 (16.3%). However, under drought had greater adjustment in osmotic potential was observed in genotype CB12702 (0.674) while, foliar spray of silicon (Silixol 0.6%) under drought had reduced the osmotic adjustment with higher change in genotype CB06803 followed by susceptible check IR64. Foliar spray of silicon (Silixol 0.6%) under drought increased the chlorophyll fluorescence parameters significantly by 11%, 6%, 6.7% and 7.7% in Fv/Fm, Y (II), ETR and qP over drought. Non-Photochemical Quenching (NPQ) increased by 48% under drought, but the foliar spray of silicon (Silixol 0.6%) under drought decreased NPQ. The grain yield per plant was observed with 30% under drought, a minimal reduction (1.9%) was observed in genotype CB13804. Foliar spray of silicon (Silixol 0.6%) under drought increased per plant yield by 23% with higher the increase (43%) in genotype CB12702. Irrespective of the genotypes, the foliar spray of silicon (Silixol 0.6%) under drought enhanced the membrane stability and plant water status in the above genotypes indicating its importance for reducing the effects of drought and improves the drought tolerance mechanism rice. The overall result revealed that the study showed drought affects the reproductive stage of the rice drastically which is alleviated with the application of silicon resulting in the betterment of membrane stability, plant water status and yield attributes. Sahbhagi Dhan a drought tolerant check performed better on drought condition and all also in foliar application of silicon under drought. Genotypes CB12702, CB06803 and CB13804 showed better performance in drought even in the absence of silicon application while with these two genotypes CB13805 also shows a better performance with foliar spray of silicon under drought might be due to alteration in the several physiological and metabolic pathways by the involvement of silicon.